Silver nanoparticles-based composite for dye removal: A comprehensive review - Siva Sankar Sana; Rajesh Haldhar; Jyotishkumar Parameswaranpillai; Murthy Chavali; Seong-Cheol Kim (Cleaner Materials, 2022)
Organic dyes are a severe threat to aquatic life. Most dyes are toxic, non-biodegradable, and likely carcinogenic. Dyes are usually removed from water via adsorption using adsorbents like wood, seaweed, algae, etc. However, traditional treatment methods are ineffective to an extent. Nanoparticles have emerged as excellent materials for dye removal due to their superb surface properties and chemical reactivity. Many different adsorbents are used today; one example is nanocomposites with embedded silver nanoparticles. In nanocomposites, silver nanoparticles embedded on graphene oxide sheets, carbon nanotubes, cellulose, orange peel, biopolymers, etc., are reported. The solid and hydrogel-based metallic and bimetallic silver nanoparticle-based nanocomposites are successful enough to degrade dyes. These nanocomposites had high reusability, stability, high surface area, tunable properties, selectivity, cost-effectiveness, excellent processability, and recyclability. For instance, AgNPS/alginate composites reported high reusability with recyclability up to 25 times. This article sheds light on the use of biopolymer composites with embedded Ag-NPs for effective dye removal. Various preparation methods as well as the kinetics of the reaction are also discussed.